Pulmonary valve prosthesis endocarditis caused by Coxiella burnetii - Kremer, Jamila; Mutters, Nico T.; Karck, Matthias; Last, Katharina (The thoracic and cardiovascular surgeon reports, 2018)
Background: Coxiella burnetii is a gram-negative bacterium assigned to the family of Rickettsiaceae. Less than 1% of Q-fever infection leads to infective endocarditis (IE). Cases of reported pulmonary valve (PV) prosthesis endocarditis are scarce. Case Description: A patient with a PV prosthesis endocarditis caused by Coxiella burnetii was seeking asylum in Germany. Prosthesis replacement was performed. All obtained blood cultures showed no growth as well as microbiological cultures of the prosthetic valve tissue. A polymerase chain reaction analysis on the explanted prosthesis detected DNA of Coxiella spp. Conclusion: Diagnosing IE caused by Coxiella burnetii requires an interdisciplinary effort from both clinicians and microbiologists.